Guru di Era Milenial dalam Bingkai Rahmatan Lil Alamin - Miftah Mucharomah (Edukasia Islamika : Jurnal Pendidikan Islam, 2017)
This study aims to portray the role of teachers in fostering the framework of Islam rahmatan lil alamin. It is worth noticing to declare that education is one of very pivotal themes in Islam. Millennial era is a digital and online era that illustrates the vast advancement of technology, including the use of social media. There is lot of information provided in the internet. On the other side, students have no ability yet to filter any information that they got. This condition encourages teachers to guide their students in filtering the internet content. This study reveals that teacher responsibilities in the millennial era are very complex. A teacher plays an important role as not only an instructor, but also an educator. It indicates that the role of teachers is not only teaching or transferring knowledge, but the most important thing is creating good behavior of the students. They are encouraged to have not only good academic qualification, but also good moral values such as rahmatan lil alamin values including humanity, cooperation, prophetic social ethic, tolerance and pluralism, balance, good modeling, dialogic pedagogy, and the enhancement of human resources.